A Unique Nanoflake‐Shape Bimetallic Ti–Nb Oxide of Superior Catalytic Effect for Hydrogen Storage of MgH2. Issue 43 (6th March 2022) - Xian, Kaicheng; Wu, Meihong; Gao, Mingxia; Wang, Shun; Li, Zhenglong; Gao, Panyu; Yao, Zhihao; Liu, Yongfeng; Sun, Wenping; Pan, Hongge
Abstract: MgH2 is one of the most promising solid hydrogen storage materials due to its high capacity, excellent reversibility, and low cost. However, its operation temperature needs to be greatly reduced to realize its practical applications, especially in the highly desired fuel cell fields. This work synthesizes a 2D nanoflake‐shape bimetallic Ti–Nb oxide of TiNb2 O7, which has high surface area and shows superior catalytic effect for the hydrogen storage of MgH2 . Incorporated with the TiNb2 O7 nanoflakes as low as 3 wt%, MgH2 shows a low onset dehydrogenation temperature of 178 °C, which is lowered by 100 °C compared with the pristine one. A dehydrogenation capacity as high as 7.0 wt% H2 is achieved upon heating to 300 °C. The capacity retention is as high as 96% after 30 cycles. The mechanism of the improved hydrogen storage properties is analyzed by density functional theory (DFT) calculation and the microstructural evolution during dehydrogenation and hydrogenation. This work provides an MgH2 system with high available capacity and low operation temperature by a unique structural design of the catalyst. The high surface area feature of the TiNb2 O7 nanoflakes and the synthesis method hopefully can develop the application of TiNb2 O7 . Abstract : A nanoflake‐shape TiNb2 O7 is synthesized by a template‐assisted solvothermal process. The obtained 2D‐TiNb2 O7 has extremely high surface area, showing high catalytic effect on the de/rehydrogenation of MgH2 . Incorporated with only 3 wt% of the TiNb2 O7 nanoflakes, MgH2 shows evidently lowered dehydrogenation temperature and a high capacity of 7.0 wt% H2 is achieved upon heating to 300 °C.